2012
DOI: 10.1097/tp.0b013e3182543950
|View full text |Cite
|
Sign up to set email alerts
|

De Novo DQ Donor-Specific Antibodies Are Associated With a Significant Risk of Antibody-Mediated Rejection and Transplant Glomerulopathy

Abstract: DQ DSAbs are associated with inferior allograft outcomes. This study shows the importance of establishing the DQ match before transplantation to define immunologic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
218
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 5 publications
9
218
0
3
Order By: Relevance
“…Studies involving pediatric and adult kidney transplant only and kidney-pancreas transplant recipients have also shown that the development of de novo donor-specific anti-HLA-DQ antibody was associated with a #10-fold greater risk of developing early and late AMR, which was often associated with development of transplant glomerulopathy and early graft loss (14)(15)(16). In our study, we have highlighted the importance of class 2 mismatches and the risk of acute rejection.…”
Section: Discussionmentioning
confidence: 69%
“…Studies involving pediatric and adult kidney transplant only and kidney-pancreas transplant recipients have also shown that the development of de novo donor-specific anti-HLA-DQ antibody was associated with a #10-fold greater risk of developing early and late AMR, which was often associated with development of transplant glomerulopathy and early graft loss (14)(15)(16). In our study, we have highlighted the importance of class 2 mismatches and the risk of acute rejection.…”
Section: Discussionmentioning
confidence: 69%
“…This observation does not necessarily challenge (25,66) the role of HLA-DQ eplet mismatches in the development of TG; but rather sheds lights on the potential diversity of eplet immunogenicity and the unique interactions of HLA-DQB/-DQA chains (in contrast to the single polymorphic HLA-DRB1 chain) with antibodies. While a greater eplet load may indicate a greater risk for experiencing antibody-mediated injuries from de novo DSA, it is the presence (or absence) of highly immunogenic eplet mismatches that help refine this risk.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing recognition that HLA antibodies are directed toward structurally defined HLA epitopes (60) rather than HLA antigens (21,25,26). Duquesnoy et al (37), for example, showed that patients with DRB1/3/4/5 antibodies were exposed to twice as many mismatched eplets as those who did not show antibodies (21.4 AE 8.0 vs. 10.6 AE 7.8, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations